Problems of pitch, pattern and harmony in the ocarina music of the Venda - Blacking, John (International Library of African Music, 1959)
This paper aims both to describe some features of Venda ocarina music and to relate these findings to a problem of method in ethno-musicology.
Keywords: South Africa; Ethnomusicology; Music; Venda (African people); Melody; Musical instruments; Ocarina; Ocarina music; Musical pitch; Africa; Harmony; African Music